Poétique de l’espace insulaire dans The Wedding de Dorothy West - Corinne Duboin (Anglophonia)
I will examine how Dorothy West reconstructs the referential space of Martha’s Vineyard, Massachussets, in her last novel, The Wedding (1995). By focusing on her fictional mapping of the island and its black enclave, the Oval, my aim is to explore West’s poetics of space with relation to her criticism of the black upper class of the Os.